STRATEGY FOR REDUCING HDPE MATERIAL PRODUCT DEFECTS IN THE INJECTION MOLDING PROCESS WITH TAGUCHI METHOD - Muhammad Ikhwan; Diana Yuliastuti (Politek ATK Yogyakarta Press, 2024)
We often encounter injection plastic products around us. Some of the advantages of plastic materials are lightweight, flexible, multipurpose, strong, not reacting, not rusty, thermoplastic (heat seal), can be colored and the price is cheap. The production process that is often used in the plastic industry is Injection Molding. In the Injection Molding process, the determination of machine parameter settings greatly affects the quality of production results. Determination of the right parameter settings can reduce the defect on the resulting product. This research was made as an effort to reduce the percentage of defects in the injection molding process with the Taguchi method. The research was conducted at the Plastic Workshop of ATK Polytechnic Yogyakarta using an Injection Molding machine type SM 90 HCV. The raw material used in this study is High-density polyethylene (HDPE) with the resulting product output in the form of packaging boxes. This study was conducted with testing samples of 90 packaged products. Based on this research, the results were obtained, among others, in the injection molding production process resulting in minimal defect values at the setting of Injection Speed level 1 10%, Injection Pressure level 3 150 bar, Plastisification (Position) level 3 180 mm and Temperature level 3 2400C. Interpretation of the results of the confirmation experiment for mean values is acceptable in consideration of the confidence interval that the results of the confirmatory experiment are smaller than the optimal results. With this, it can be concluded that this research can be implemented to improve the quality of packaging products for the Injection Molding Process.